simplify ( x³ - 2x² + 5x - 7 ) ( 2x - 3 )
Answers
Answered by
8
Hey!
![(x^3-2x^2+5x-7) (2x-3)\\=2x(x^3-2x^2+5x-7)-3(x^3-2x^2+5x-7)\\=2x^4-4x^3+10x^2-14x-3x^3+6x^2-15x+21\\=\boxed{\boxed{2x^4-7x^3+16x^2-29x+21}} (x^3-2x^2+5x-7) (2x-3)\\=2x(x^3-2x^2+5x-7)-3(x^3-2x^2+5x-7)\\=2x^4-4x^3+10x^2-14x-3x^3+6x^2-15x+21\\=\boxed{\boxed{2x^4-7x^3+16x^2-29x+21}}](https://tex.z-dn.net/?f=%28x%5E3-2x%5E2%2B5x-7%29+%282x-3%29%5C%5C%3D2x%28x%5E3-2x%5E2%2B5x-7%29-3%28x%5E3-2x%5E2%2B5x-7%29%5C%5C%3D2x%5E4-4x%5E3%2B10x%5E2-14x-3x%5E3%2B6x%5E2-15x%2B21%5C%5C%3D%5Cboxed%7B%5Cboxed%7B2x%5E4-7x%5E3%2B16x%5E2-29x%2B21%7D%7D)
duragpalsingh:
is it correct?
Answered by
7
2x (x^3-2x^2+5x-7)-3 (x^3-2x^2+5x-7)
2x^4-4x^3+10x^2-14x-3x^3+6x^2-15x+21
2x^4-4x^3-3x^3+10x^2+6x^2-14x-15x+21
=2x^4-7x^3+16x^2-29x+21
hope it help u...
2x^4-4x^3+10x^2-14x-3x^3+6x^2-15x+21
2x^4-4x^3-3x^3+10x^2+6x^2-14x-15x+21
=2x^4-7x^3+16x^2-29x+21
hope it help u...
Similar questions